Past peak prominence: the changing role of integrated assessment modelling in the IPCC - Gusheva, Ema; Pfenninger, Stefan; Lilliestam, Johan (iScience, 2024)
The main task of the Intergovernmental Panel on Climate Change (IPCC) is to provide comprehensive as- sessments of climate science. However, there are accusations of bias toward certain research fields based on limited empirical evidence. By analyzing the evidence base of Working Group 3 (WG3) reports, we show that integrated assessment modeling (IAM) research was influential in all six assessments, and over- represented in the Summary for Policymakers (SPM). Further, we show that a small number of men work- ing in Western Europe and the USA dominate IAM research. Thus, global climate negotiations and science may have historically prioritized mitigation solutions suggested by an unrepresentative scientific sample and missed solutions from other perspectives like those of females and non-Western cultures. However, we also show that IAM research influence decreased in AR6, implying a leveling playing field between research fields. But more effort is needed to ensure a comprehensive assessmen